Presentism and History in Music Education: What Content for What Future? – Position papers - Giuseppina La Face; Paolo Somigli (Musica Docta)
The two position papers, Presentism and History in Music Education: What Content for What Future? by Giuseppina La Face (pp. 1-2) and Necessità della storia della musica by Paolo Somigli (pp. 2-6), contextualize the reasons and cultural objectives of the meeting held in Catania in May 2023, Presentism and History in Music Education: What Content for What Future? In particular, they emphasise the need for historical perspective and knowledge of the history of art music as a heritage to be received and transmitted, and as a tool for understanding history and current events.